Political Situation in Belgium and France: Trends and Limits of the Right-wing Populist Turn - Alexandra Zhidkova; Alexandra Khorosheva (Современная Европа, 2025)
The trend toward strengthening right-wing populist parties is relevant for many European countries. That fact poses a number of questions related to both the reasons for such an upward trend and the possibility to talk about right-wing populists as a single political family. The right-wing turn, based primarily on the electoral successes of right-wing populists and far-right forces, has also affected two close countries ‒ Belgium and France. The resemblance of the political processes taking place in these countries is not limited exclusively to their geographic location, but also it is associated with the similarity of political tradition and the stable inclusiveness of right-wing populists in relation to the traditional parties. The purpose of the article which compares the right-wing populist turn in Belgium and France consists of several aspects. First of all, the authors show how the right-wing populist parties were formed and what are the key elements of their ideology. The article examines the problem of institutionalization of right-wing populists in both countries and the comparable systemic isolation of such parties. The article analyzes the position of right-wing populists of Belgium and France on the European political scene, as well as how the European policy of these parties is influenced by the perception of the European integration project. The analysis is based on social surveys and Eurobarometer data. Finally, the authors demonstrate how the results of the European elections 2024 at the national level in Belgium and France correlate with European trends.